1952
DOI: 10.1001/jama.1952.72930350001009
|View full text |Cite
|
Sign up to set email alerts
|

Cholelithiasis and Perforation of the Gallbladder in an Infant, With Recovery

Abstract: Cholecystitis with cholelithiasis is an unusual finding in infancy, but the condition has been reported several times in the literature of the last 200 years; however, it has always been an autopsy finding, and no case could be found that had been diagnosed during life and treated, with subsequent recovery, in an infant under 1 year of age. REPORT OF A CASEA 6-weeks-old female infant was admitted to the Los Angeles Childrens Hospital with a diagnosis of intestinal obstruction. At 2 weeks of age the baby began … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1954
1954
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Various surgical procedures have been reported as follows: (1) intraperitoneal drainage only , (2) biliary drainage through a perforation site , (3) construction of a tube biliary fistula, (4) suture closure of the perforation site , (5) closure by placing a gallbladder patch on the perforation site, (6) sewing a caulescent gallbladder wall as a patch on the perforation site , T tube insertion into the common bile duct, (7) cholecystoduodenostomy or cholecystojejunostomy , (8) if the perforation site is the gallbladder, cholecystectomy; if the perforation site is the bile duct, choledochojejunostomy (choledochoduodenostomy), (9) choledochojejunostomy (choledochoduodenostomy), (10) T tube biliary fistula, (11) extrahepatic biliary resection after several months , (12) extrahepatic biliary resection according to the general physical condition of the patient , etc.…”
Section: Chapter Iv: Treatments and Diagnosismentioning
confidence: 99%
“…Various surgical procedures have been reported as follows: (1) intraperitoneal drainage only , (2) biliary drainage through a perforation site , (3) construction of a tube biliary fistula, (4) suture closure of the perforation site , (5) closure by placing a gallbladder patch on the perforation site, (6) sewing a caulescent gallbladder wall as a patch on the perforation site , T tube insertion into the common bile duct, (7) cholecystoduodenostomy or cholecystojejunostomy , (8) if the perforation site is the gallbladder, cholecystectomy; if the perforation site is the bile duct, choledochojejunostomy (choledochoduodenostomy), (9) choledochojejunostomy (choledochoduodenostomy), (10) T tube biliary fistula, (11) extrahepatic biliary resection after several months , (12) extrahepatic biliary resection according to the general physical condition of the patient , etc.…”
Section: Chapter Iv: Treatments and Diagnosismentioning
confidence: 99%
“…The etiology for gallbladder perforation during infancy is unknown except for cholelithiasis [3,5]. Gull et al [2] suggested that perinatal asphyxia and sepsis with resulting splanchnic ischemia might be a possible cause for neonatal gallbladder perforation.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have been only 4 cases of gallbladder perforation reported in infants or neonates [2][3][4][5]. The etiologies for gallbladder perforation during infancy remain idiopathic except for cholelithiasis [3,5]. Fundus is the most common site of the perforation.…”
mentioning
confidence: 99%
“…The literature has documented about 25 cases, of which 9 were seen in association with an epidemic of neonatal enteritis caused by Salmonella enteritidis [111]. Of the remaining infants, 16 were the subjects of isolated case reports [24,103,[112][113][114][115][116][117][118][119][120][121][122][123], and 3 died of other causes with inflammatory changes in the gallbladder described as an incidental finding at autopsy [81,95,124]. A tissue diagnosis of "chronic cholecystitis" was established in an infant whose biliary disease apparently began at 6 days of age [125].…”
Section: Infections Of the Biliary Tractmentioning
confidence: 99%
“…The pathogenesis of this condition is uncertain; all but three cases [99,118,122] of cholecystitis in the newborn period have been acalculous. It is postulated that sepsis, dehydration, prolonged fasting (e.g., total parenteral nutrition), congenital obstruction, or a stone impacted in the cystic duct leads to biliary stasis and acute distention of the gallbladder.…”
Section: Infections Of the Biliary Tractmentioning
confidence: 99%